2016
DOI: 10.1007/978-94-017-7537-3_2
|View full text |Cite
|
Sign up to set email alerts
|

Allergic Contact Dermatitis: A Model of Inflammatory Itch and Pain in Human and Mouse

Abstract: This chapter is an overview of published observations from our laboratory on the psychophysics and neurobiology of the persistent itch and pain of allergic contact dermatitis (ACD). ACD is a clinically significant problem with many features characteristic of other pruritic disorders. Our approach was to produce ACD experimentally in humans and in the mouse. The goal was to use the mouse as an animal model for investigating the peripheral neural mechanisms of itch and pain of ACD in humans. Humans and mice were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…We showed that repetitive oxazolone challenge on mouse cheek provokes both scratching (with hindpaw) and wiping (with forepaw) behavior, which could be interpreted as itch and pain sensation, respectively [13]. Consistent with our findings, studies from LaMotte's lab also found that the contact sensitizer squaric acid dibutyl ester-induced ACD model mice developed similar itch-and pain-related behaviors [2,38]. These studies support the notion that ACD model mice developed a mixed itch and pain sensation.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…We showed that repetitive oxazolone challenge on mouse cheek provokes both scratching (with hindpaw) and wiping (with forepaw) behavior, which could be interpreted as itch and pain sensation, respectively [13]. Consistent with our findings, studies from LaMotte's lab also found that the contact sensitizer squaric acid dibutyl ester-induced ACD model mice developed similar itch-and pain-related behaviors [2,38]. These studies support the notion that ACD model mice developed a mixed itch and pain sensation.…”
Section: Discussionsupporting
confidence: 85%
“…Allergic contact dermatitis is a type of skin disease involving overreactivity of skin to contact allergens, accompanied with skin inflammation and mixed pain and itch sensations [1][2][3][4]. ACD is triggered by sensitization and subsequent contact with allergens, which may originate from occupational, environmental, or nutritional sources [5].…”
Section: Introductionmentioning
confidence: 99%
“…Mechanosensitive channel activation sensitivity is an important feature of all mechanosensitive channels. Overactive mechanosensitive channels may lead to deleterious effects ranging from a loss in cell volume in bacteria or red blood cells (Cahalan et al, 2015; Levin and Blount, 2004) to persistent itch disease in higher organisms (LaMotte, 2016). Membrane composition has been increasingly shown to modulate the force-from-lipids activation of mechanosensitive channels and this effect is hypothesized to be due to changes in global membrane properties (Bruno et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…ACD is also an example of diseases characterized by persistent itch in contrast to transient itch and accompanying nociceptor responses. Less is known about the nociceptor activity during itch lasting for days or longer ( 19 ).…”
Section: Mast Cell-mediated Itch In Acdmentioning
confidence: 99%